IDE MANUSIA TERBELENGGU MENURUT SWAMI VIVEKANANDA DAN ARTHUR SCHOPENHAUER SERTA IMPLIKASI ETISNYA - Tampubolon, Guruh David Agus (Sanjiwani: Jurnal Filsafat, 2024)
Jean-Paul Sartre (1905-1980) stated that humans are destined to act freely. Plautus in 195 BC said that man is a wolf to his fellow man, in other words, humans tend to be bound to will evil rather than otherwise. Philosophers are divided into more optimistic or more pessimistic sides in viewing humans. Swami Vivekananda and Arthur Schopenhauer both have a pessimistic view of life and humanity. This article focuses on examining the ideas of Schopenhauer and Vivekananda regarding the bondage of humans. Finally, the author wants to know the ethical implications that arise if starting from their corresponding views? This research is qualitative, explanatory, and a literature study. Arthur Schopenhauer sees life as endless suffering and this stems from the irrational noumena of the Will and life as a comedy and tragedy. He himself also acknowledged being inspired by Hindu Vedanta teachings. Vivekananda, as an important figure who brought Vedanta to Europe, once criticized Schopenhauer regarding the nature of the ‘will.’ However, Vivekananda also had pessimism regarding humans with the existence of maya, human knowledge and ‘manas’ being bound, ‘karma’, ‘samsara’, ‘klesa’, and the trinity of ignorance, will, and inequality. Therefore, even though they are not exactly the same in terms of the nature of human will, Vivekananda and Schopenhauer both emphasize the idea of human bondage. The ethical implication is that humans need consciousness to resolve their own moral struggles or the determination of awareness from something outside themselves.